2009
DOI: 10.21273/hortsci.44.6.1522
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing between ‘Bacon’ Pollinizers and Adjacent ‘Hass’ Avocado Trees and the Description of Two New Lethal Mutants

Abstract: Avocado (Persea americana Mill.) has an unusual flowering mechanism, diurnally synchronous protogynous dichogamy, that promotes crosspollination among avocado genotypes. In commercial groves, which usually contain pollinizer rows adjacent to the more desirable commercial cultivars, the rate of outcrossing has been measured with variable results. Using microsatellite markers, we estimated outcrossing in a commercial California ‘Hass’ avocado orchard with adjacent ‘Bacon’ polli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Fruit were collected from selected trees that were among 350 unique 'Hass' · 'Bacon' and 'Bacon' · 'Hass' hybrid trees planted at the USHL-ARS, Fort Pierce, FL, in 2008 on double row beds in Riviera fine sand soil type. Trees originated from seeds collected from a commercial orchard in California by Dr. Raymond Schnell (SHRS-ARS, Miami), and molecular marker analysis confirmed which seedlings were true 'Hass'-'Bacon' hybrids before planting (Schnell et al, 2009). The trees were sprayed with horticultural oil and copper (CS-2005; Magna-Bon II, LLC, Okeechobee, FL), received foliar fertilization with a 20N-10P-20K soluble fertilizer every 2 weeks as part of a regular maintenance regimen, and received annual granular dry fertilizer (12N-2P-14K) at 226-270 kg · ha -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Fruit were collected from selected trees that were among 350 unique 'Hass' · 'Bacon' and 'Bacon' · 'Hass' hybrid trees planted at the USHL-ARS, Fort Pierce, FL, in 2008 on double row beds in Riviera fine sand soil type. Trees originated from seeds collected from a commercial orchard in California by Dr. Raymond Schnell (SHRS-ARS, Miami), and molecular marker analysis confirmed which seedlings were true 'Hass'-'Bacon' hybrids before planting (Schnell et al, 2009). The trees were sprayed with horticultural oil and copper (CS-2005; Magna-Bon II, LLC, Okeechobee, FL), received foliar fertilization with a 20N-10P-20K soluble fertilizer every 2 weeks as part of a regular maintenance regimen, and received annual granular dry fertilizer (12N-2P-14K) at 226-270 kg · ha -1 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been assumed that Persea americana demonstrates outcross pollination as a result of its floral dichogamy. However, different studies have shown that a high rate of self-pollination in avocado may be possible (Borrone et al, 2008;Garner et al, 2008;Kobayashi et al, 2000;Schnell et al, 2009). The differences in the resistance levels presented among the genotypes are a result of not only the high genetic variability found in individuals coming from the seed as a result of open pollination (Andrade-Hoyos et al, 2015), but also the level of pathogenicity presented by P. cinnamomi (Ochoa-Fuentes et al, 2015) and the interaction between these in an environment beneficial to disease development.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular markers in avocado have been used to assess genetic diversity among and within racial groups (Boza et al, 2018;Cuiris-P erez et al, 2009;Gross-German and Viruel, 2013), in phylogenetic studies (Ashworth and Clegg, 2003;Reyes-Alem an et al, 2013), and in construct linkage maps ; to identify quantitative trait loci (Sharon et al, 1998), and in outcrossing studies (Alcaraz and Hormaza, 2011;Borrone et al, 2008;Chen et al, 2007;Garner et al, 2008;Kobayashi et al, 2000;Schnell et al, 2009;Violi et al, 2009). Outcrossing rate studies based on molecular markers have been done in different plant species such as Brassica carinata A. Braun (Teklewold et al, 2013), Foeniculum vulgare Mill.…”
mentioning
confidence: 99%
“…In avocado, most outcrossing studies have been done in cultivars such as Hass, Bacon, Zutano, and others (Kobayashi et al, 2000;Schnell et al, 2009) to detect potential donors of pollen and to calculate the correlation between outcrossing and yield (Kobayashi et al, 2000), to determine the incidence and effectiveness of self-and cross-pollinated avocado fruit (Davenport et al, 2006), and to assess the relation among outcrossing rate with yield and alternate bearing (Garner et al, 2008). In addition, the outcrossing rate has been used to assess the proportion of progeny resulting from parents with complementary blooming (Borrone et al, 2008;Violi et al, 2009) and to determine whether an outcrossed progeny is more tolerant to Phytophthora root rot than a self-pollination progeny ).…”
mentioning
confidence: 99%